DELIK HUKUM DALAM PERSPEKTIF FILSAFAT HUKUM ISLAM - Wirawan, Vani (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
Studying philosophy seems to be in a very abstract realm in the realm of ontology, epistemology and axiology related to something, and philosophy of law is a branch of philosophy that has a strategic function in the formation of law in Indonesia. This study aims to determine legal offenses in the view of Islamic legal philosophy. The research writing method used is normative legal research with a conceptual approach. The results of the study indicate that the realm of ontology, offense in Islamic criminal law has a fundamental difference compared to conventional criminal law in reality in the form of jinayah, jarimah, and qisas-diyat. The realm of epistemology, offense in Islamic criminal law focuses on how knowledge about crime is obtained, understood, and applied derived from sources of revelation such as the Qur'an and Hadith, as well as methods of understanding through ijtihad by Islamic jurists. The realm of axiology, offense in Islamic criminal law is related to the values of justice, benefit, and social justice aims to ensure that criminal sanctions are not only retributive, but also oriented towards community rehabilitation and the achievement of welfare